A pilot study on electronic health record use in the community pharmacy setting - Convento, Karen Michelle M.
The concept of Electronic Health Records (EHR) has been implemented in countries such as U.S, U.K. Japan, Singapore and Australia for enhanced patient care in community pharmacy. In the Philippines, there has been a problem on lack of patient records in a community pharmacy setting. In order to address this problem, the researchers have conducted a pilot study of EHR in Alabang, Muntinlupa. The study was composed of three phases, namely, Phase I for Planning and Design Phase; Phase II or Implementation Phase and Phase III, the Evaluation Phase. The sources of data for Phase I included the community pharmacists in Alabang for needs assessment survey on EHR use and the PPhA president for expert's opinion on EHR for its content, functionalities, features as well as the layout. Phase II included the identification of drug therapu problems using the EHR for qualified hypertensive patients and Phase III for the evaluation of the implementing pharmacists through interview and the evaluation of patients through survey questionnaire and phone interview. Results on needs assessment from Phase I suggested that EHR is non-existent in the community pharmacy workplace and all of the pharmacists surveyed were willing to be trained for at least two hours of their time. Moreover, for the pharmacist's acceptability of EHR, with sub-categories, such as, EHR is expected to be easy, being skilled in using EHR, ease of use for pharmacist and familiarity with computers, have obtained a positive or agreeable answer for all. Acceptability with subcategories such as: the job will be easier, professional satisfaction and continuity of care have also gotten a positive or agreeable response for all as well as for EHR usage. 73% of those surveyed said that having a patient oriented pharmaceutical care was the perceived strength of this program while the perceived barrier was being time consuming. Expert's opinion pointed out the primary information needed for EHR service, having a simple field of EHR, strategies for advertisement, possible patient concerns and possible drugstore owner's concern. Upon content analysis of the gathered information, the researchers created the EHR database using MS Access 2010 and Microsoft Visual Basic for applications. Phase II resulted to 20.7% hypertensive patient participation who were identified to have potential drug interaction and found to be non-adherent to their medication regiment. Upon the evaluation of these patients enrolled in the program for Phase III, all of them agreed that EHR system took a lot of time but they can also agreed that there were no violations made on their confidentiality. In the light of the results, there is a need for an EHR system in community pharmacies. The positive perceptions obtained during the development and implementation of the EHR software including the comments of end-users pertaining to increased rate of acceptability are important considerations in the enhancement of the system and appreciation of the community pharmacists.